Preparation and identification of multifunctional mesoporous silica nanoparticles for in vitro and in vivo dual-mode imaging, theranostics, and targeted tracking. (April 2015) - Chan, Ming-Hsien; Lin, Hsiu-Mei
Abstract: Mesoporous silica nanoparticles (MSNs) can provide a structural foundation for a new generation of nanocarriers with a broad range of functionalities. Multifunctional MSNs can serve as all-in-one diagnostic and therapeutic tools that can be used to simultaneously visualize and treat various diseases, such as cancer. This research study is the first time that two lanthanide-based imaging systems have been combined to incorporate controlled drug release and targeted tracing into a single MSN-based nano-platform for a novel theranostic drug delivery system. Doping lanthanide ions, i.e., europium (Eu) and gadolinium (Gd) ions, into an MSN structure (EuGd-MSNs) imparts fluorescence and magnetism to the nanostructure that can be used to develop magnetic resonance imaging (MRI) and biological fluorescence tools. Current cancer research has revealed that most human cancer cells express a large number of folate receptors on their surface. Grafting folic acid (FA) onto the EuGd-MSN surface (EuGd-FA-MSNs) imparts a targeting function to the MSN because of the specificity of the binding of FA to cell surface receptors. Furthermore, grafting anticancer drugs, such as camptothecin (CPT), onto the surface of these MSNs by forming disulfide bonds (EuGd-SS-CPT-FA-MSNs) enables intracellular controlled drug release. A high concentration of intracellular glutathione cleaves the disulfide bond to release the drug and treat the disease. The results of in vitro and in vivo studies show that the functionalized MSNs can be successfully used as a platform to integrate dual-imaging, targeting, and therapeutic treatment in multifunctional diagnosis drug delivery systems.